European public space projects with social cohesion in mind: symbolic, programmatic and minimalist approaches. Issue 6 (3rd June 2022) - Simões Aelbrecht, Patricia; Stevens, Quentin; Kumar, Sanjeev
ABSTRACT: The last two decades have witnessed a growing commitment to European public space projects seeking to promote social cohesion. These projects are built on the premise that social cohesion is under threat from the increasing cultural and economic differences in contemporary cities, and that it should be promoted through public spaces. This paper examines the key commonalities and differences among these new public space projects, in terms of their social, economic and planning policy contexts, social goals, design aims, processes and outcomes, and their diverse representational and use needs. The paper characterizes three distinct open space design approaches – Symbolic, Programmatic and Minimalist – that governments and designers that have put forward as best practices to enhance social cohesion, which have all been applied in similar socio-cultural and urban contexts: multicultural, low-income neighbourhoods that are experiencing gentrification. By combining theories and methods from urban design and social sciences, this paper offers an assessment and comparison of the three case studies and their relative merits and limitations in terms of how they used public space design to support the divergent functional and representational needs of diverse social groups, and the common aim of enhancing cohesion among these groups.